Implementasi Pendidikan Nilai Kebangsaan Melalui Ekstrakurikuler Hizbul Wathan Di SD Muhammadiyah 2 Kauman Surakarta Tahun Ajaran 2015/2016 - Budi Santoso, Arif; , Dra. Risminawati, M.Pd; , Drs. Saring Marsudi, SH., M.Pd (2016)
This study aims to determine: (1) the value of nationality which is implemented through extracurricular Hizbul wathan in SD Muhammadiyah 2 Surakarta Kauman. (2) how to implement the national values education through extracurricular Hizbul wathan in SD Muhammadiyah 2 Surakarta Kauman. (3) the factors supporting and hindering the implementation of national values education through extracurricular Hizbul wathan in SD Muhammadiyah 2 Surakarta Kauman .This research is qualitative research. Decision informants using purposive technique. Data collection techniques in this study consisted of direct observation, interview and documentation. For the validity of the data using a triangulation of data or sources of triangulation method. Data analysis technique used is an interactive model. Based on the results of this study concluded that the implementation of national values education through extracurricular Hizbul Wathan Kauman At SD Muhammadiyah 2 Surakarta Academic Year 2015/2016 planting is carried out through national and state consciousness, love of the homeland, the belief in Pancasila, willingness to sacrifice for the nation and the State as well as the ability beginning of defending the country. values are developed that religious values, Rasa Cinta Tanah Air, discipline, self-reliance, courage and responsibility. While the method to be implemented Education Nationality Value Through Ekstrakurikuier Hizbul Wathan ie by example, habituation, and educational games. Factors Supporting Education Implementation Nationality Value Through Extracurricular Hizbul Wathan in SD Muhammadiyah 2 Kauman are: Support from the school, especially the principal, Competence Trustees Hizbul Wathan adequate Interests high student in following Extracurricular Hizbul Wathan, support parents to students in the form of moral and materially. While the inhibiting factors Implementation Nationality Value Through Extracurricular Hizbul Wathan in SD Muhammadiyah 2 Kauman is Facilities and infrastructure supporting extracurricular activities were inadequate and the monitoring of the parents to the student when the home has not been able to follow what is being taught in school when the teacher. Keyword : education, national values, exctracurricular, hizbul wathan